The Article of 'High Achievers' Use of Self-Talk as a Strategy in Speaking - Clarissa, Angela Nova (Universitas Negeri Surabaya, 2022)
Speaking in public for academic purposes is one of the most fear that undergraduate students suffer from, especially student teachers. For that case, researchers have proposedseveral strategiesfor public speakingincluding self-talk that could help students to bebetter speakers. The purpose of this study isto understand the way high-achiever students do self-talk fortheir speech performances and the frequency of their self-talk. Usingbasic qualitative data analysis, this study investigatedwhich type of self-talkhigh-achiever students’use and their way to do their self-talkduring speech performances.The research gap from existing studies is that this research elaborate focused participants, which only aimed to understand high achievers students. The researcher usedtheself-talk concept from Brinthauptas the primary theory and utilized it to determine the participants’ type of self-talk.The participants for this study were four high achiever undergraduate students. The result of this study wasthat all of the participants used self-management, there was no self-criticism found, and the frequency of the participants’ self-talk affected their communication apprehensive.